The International Encyclopedia of Organizational Communication 2017
DOI: 10.1002/9781118955567.wbieoc219
|View full text |Cite
|
Sign up to set email alerts
|

Work–Life Balance

Abstract: Communication studies research on work–life balance takes a constitutive approach that communication constitutes work–life enactments, and that work–life enactments differ based on economic systems, political landscapes, gender ideologies, cultural values and attitudes, history, and governmental support. This research spans from broad studies of societal constructs such as ideal workers and gendered norms, to organizational constructs such as work–life “cultures” and policies, to interpersonal studies of how i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Of the total benefit responses (n = 178), most participants noted life-related benefits, with 73.6 percent (n = 131) identifying spending time with family (e.g., spending time with kids, using time to reconnect with family) and 72.5 percent (n = 129) identifying more personal time (e.g., time for hobbies, reflection, and self-development). Participants' interpretations of work efficiencies perpetuated cultural scripts related to productivity (Kirby, 2017) and demonstrated that they drew on their past experiences with familiar discourses to understand their new experience (Weick, 1995). However, par-ticipants suggested that their work efficiencies were helpful in creating more time for life rather than more work time, which is a departure from historical US work-life discourses (see Kirby, 2017 for discussion).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the total benefit responses (n = 178), most participants noted life-related benefits, with 73.6 percent (n = 131) identifying spending time with family (e.g., spending time with kids, using time to reconnect with family) and 72.5 percent (n = 129) identifying more personal time (e.g., time for hobbies, reflection, and self-development). Participants' interpretations of work efficiencies perpetuated cultural scripts related to productivity (Kirby, 2017) and demonstrated that they drew on their past experiences with familiar discourses to understand their new experience (Weick, 1995). However, par-ticipants suggested that their work efficiencies were helpful in creating more time for life rather than more work time, which is a departure from historical US work-life discourses (see Kirby, 2017 for discussion).…”
Section: Resultsmentioning
confidence: 99%
“…The dominant US discourses about work provide a context within which to understand the communication shifts regarding work and private life that occurred during the COVID-19 pandemic stay-at-home orders. In the US, work has historically been privileged over private life (Kirby, 2017). Even in cases where there are physical boundaries to separate the work and private spheres, work frequently permeates into people's private lives, whereas the boundaries around work resist interference from life (Pal et al, 2020).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has illustrated the connection of work-related time commitment with WLC, as work-family conflicts increase with working more in a given week ( Pleck et al, 1980 ; Greenhaus and Beutell, 1985 ). Strain-based WLC refers to the fact that stressors in one domain (e.g., work) lead to negative emotions and physical strain (e.g., tension, anxiety, depression, energy depletion), which reduces one’s capacity to accomplish their roles in the other domains (e.g., personal life; Greenhaus and Beutell, 1985 ; Steiber, 2009 ; Kirby, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kirby (2017) mentions the significance of understanding how work–life balance differs across social representations due to economic systems, political backgrounds, gender philosophies, socio-cultural ethos, experiences and possibly governmental support. Similarly, Kamenou (2008) stresses that there is limited research around ethnicity, culture, religion and careers of older or disabled people, from the mainstream discussions of work–life balance.…”
Section: Introductionmentioning
confidence: 99%